2006
DOI: 10.1002/elps.200600401
|View full text |Cite
|
Sign up to set email alerts
|

Use of micromolded carbon dual electrodes with a palladium decoupler for amperometric detection in microchip electrophoresis

Abstract: The fabrication and evaluation of micromolded dual carbon ink electrodes and their integration with a fabricated palladium decoupler for use in microchip electrophoresis is described. As opposed to previous work involving carbon-based dual electrodes with microchip electrophoresis, this approach results in electrodes that are amenable to mass production in a manner where the decoupler/electrode alignment is fixed and reproducible. In this work, electrode sizes and spacings were optimized to result in dual carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(101 citation statements)
references
References 38 publications
3
98
0
Order By: Relevance
“…The increased detection sensitivity was reflected in low LOD values: 0.25 and 0.5 mM for dopamine and catechol, respectively. The properties of an electrophoretic chip with a Pd decoupler and a couple of carbon electrodes prepared by a screen printing technique were studied in [29]; the testing substances were again neurotransmitters in a mixture with ascorbic acid.…”
Section: Direct Dection -Mode 2 In Chip Electrophoresismentioning
confidence: 99%
“…The increased detection sensitivity was reflected in low LOD values: 0.25 and 0.5 mM for dopamine and catechol, respectively. The properties of an electrophoretic chip with a Pd decoupler and a couple of carbon electrodes prepared by a screen printing technique were studied in [29]; the testing substances were again neurotransmitters in a mixture with ascorbic acid.…”
Section: Direct Dection -Mode 2 In Chip Electrophoresismentioning
confidence: 99%
“…The results indicated that this dual EC and ECL detection strategy could provide a simple and convenient detection method for analysis of more kinds of analytes in CE separation than the single EC or ECL detection alone, and more information of analytes could be achieved in analytical applications simultaneously. Amperometric detection with dual electrodes on microchip also has been investigated by several researchers [49][50][51]. Obviously, there existed a little distance between the two detector cells in the dual detection schemes which have been reported in microfluidic systems [46,47,50,51] except the coupling of EC and ECL [48], which led to the response of the double detections not happening at the same time exactly.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the multiplexing detection which could make up for the shortages of single detection and give more information about the analytes has received much attention. A variety of dual detection schemes have been proposed for capillary electrophoresis [33][34][35][36][37][38][39][40][41][42][43][44][45], while relatively less in connection with microfluidic chips [46][47][48][49][50][51]. Wang et al [46] described the performance characteristics and advantages of a new dual electrochemical (EC) microchip detection system based on simultaneous conductivity and amperometric measurements.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been several approaches that include placing the electrodes in a reservoir [11, 12], it has been shown that a simple and reproducible method to perform this integration is through the use of a palladium “decoupler” electrode that is incorporated within the fluidic network to provide an electrophoretic ground and adsorb hydrogen produced from the reduction of water at the cathode [10, 1316]. This approach enables a downstream working electrode to remain in the fluidic network, which helps to minimize band broadening processes that occur when electrodes are placed in a reservoir [12, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…To do this with traditional fabrication techniques would require multiple sputtering/patterning steps with precise mask alignment. This has led our group to use carbon ink electrodes that are molded onto the electrode plate after the palladium decoupler has been patterned [3, 10, 23, 28]. Finally, thin-layer electrodes typically used for microchip applications are not able to be polished to generate a fresh electrode surface as is the case with both traditional electrode materials and electrochemical flow cells used for liquid chromatography.…”
Section: Introductionmentioning
confidence: 99%